2021
DOI: 10.3390/ijerph182010663
|View full text |Cite
|
Sign up to set email alerts
|

Regional Characteristics of the Second Wave of SARS-CoV-2 Infections and COVID-19 Deaths in Germany

Abstract: (1) Background: In the absence of individual level information, the aim of this study was to identify the regional key features explaining SARS-CoV-2 infections and COVID-19 deaths during the upswing of the second wave in Germany. (2) Methods: We used COVID-19 diagnoses and deaths from 1 October to 15 December 2020, on the county-level, differentiating five two-week time periods. For each period, we calculated the age-standardized COVID-19 incidence and death rates on the county level. We trained gradient boos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…The earliest start date was 1 January 2020 [ 12 , 29 , 37 ], and the latest start date was 1 October 2020 [ 43 ]. The mean observation period across the included studies was 23.4 weeks, with a median period of 19.9 weeks and a period range of 3.9–59.9 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The earliest start date was 1 January 2020 [ 12 , 29 , 37 ], and the latest start date was 1 October 2020 [ 43 ]. The mean observation period across the included studies was 23.4 weeks, with a median period of 19.9 weeks and a period range of 3.9–59.9 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Hoebel et al found similar patterns at the district level during the second pandemic wave in Germany [ 10 ]. However, Doblhammer et al used a different, machine-learning–based approach to identify socioeconomic indicators combined into composite measures and their impact on COVID-19 cases at the district level during the second pandemic wave in Germany [ 43 ]. Although the analytical approach differed from that of Hoebel et al, the authors found similar patterns, indicating that less deprived areas were more strongly correlated with cases at the beginning of the second wave but the correlation later reversed to the detriment of more deprived areas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lippold et al [22] have used countylevel data to provide predictions for future spread. Doblhammer et al [10] showed that during the second wave, political affiliations and socioeconomic indicators were associated with higher incidences of SARS-CoV-2. A recent estimation of spreading dynamics of SARS-CoV-2 in Germany assessed regional heterogeneity in the effectiveness of measures on infection dynamics and identified three distinct regional clusters of spreading patterns [29].…”
Section: Discussionmentioning
confidence: 99%
“…Other unobserved characteristics at the regional or individual level can explain observed relationships, too. In the beginning of 2021, regional variation in concerns could for example also be a product of different regional predominant political orientations across Germany [ 69 ] which we cannot measure and control for adequately.…”
Section: Discussionmentioning
confidence: 99%